PENGARUH EFIKASI DIRI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA STIE PEMBANGUNAN TANJUNGPINANG - Yuritanto Yuritanto; Armansyah Armansyah (Jurnal Inovasi Penelitian, 2021)
This study aims to see and analyze the effect of Self Efficacy and Entrepreneurial Knowledge on Entrepreneurial Interest in STIE Pembangunan Tanjungpinang students. The sample of this research is 80 students of Management Study Program Morning Class 2 and 1 class 2020/2021 with saturated sample method. The data analysis method used is descriptive analysis and Multiple Linear Regression analysis, t test and F test. The results show that the Self Efficacy variable partially has a positive and significant effect on Entrepreneurial Interest, the Entrepreneurial Knowledge variable partially has a positive and significant impact on Entrepreneurial Interest. and the variables of Self Efficacy and Entrepreneurial Knowledge together have a positive and significant effect on Entrepreneurial Interest in STIE Pembangunan Tanjungpinang students. From the results of the analysis of the determinant coefficient, the R Adjusted Square (R2) value of 0.401 means that 40.10% of the Entrepreneurial Interest variable can ensure the Self Efficacy and Entrepreneurial Knowledge variables while the remaining 50.90% can be identified by other variables not examined in this research.